POLITICAL ROLE IN A DEMOCRATIC COUNTRY (International Journal of Food and Nutritional Sciences, 2022)
A central claim of democratic theory is that democracy induces governments to be responsive to the preferences of the people. Political parties organize politics in every modern democracy, and some observers claim that parties are what induce democracies to be responsive. Yet, according to others, parties give voice to extremists and reduce the responsiveness of governments to the citizenry. The debate about parties and democracy takes on renewed importance as new democracies around the globe struggle with issues of representation and governability. I show that our view of the impact of parties on democratic responsiveness hinges on what partiesare their objectives and organization. I review competing theories of parties, sketch their testable implications, and note the empirical findings that may help adjudicate among these theories. I also review debates about the origins of parties, about the determinants of party-system size and characteristics, and about party competition.